CD11b+CD43hiLy6Clo splenocyte‐derived macrophages exacerbate liver fibrosis via spleen–liver axis. Issue 5 (17th May 2023) - Zhang, Shaoying; Wan, Dan; Zhu, Mengchen; Wang, Guihu; Zhang, Xurui; Huang, Na; Zhang, Jian; Zhang, Chongyu; Shang, Qi; Zhang, Chen; Liu, Xi; Liang, Fanfan; et al.
Abstract : Background and Aims: Monocyte‐derived macrophages (MoMFs), a dominant population of hepatic macrophages under inflammation, play a crucial role in liver fibrosis progression. The spleen serves as an extra monocyte reservoir in inflammatory conditions; however, the precise mechanisms of involvement of the spleen in the pathogenesis of liver fibrosis remain unclear. Approach and Results: By splenectomy and splenocyte transfusion, it was observed that splenic CD11b + cells accumulated intrahepatically as Ly6C lo MoMFs to exacerbate CCl4 ‐induced liver fibrosis. The splenocyte migration into the fibrotic liver was further directly visualized by spleen‐specific photoconversion with KikGR mice and confirmed by CD45.1 + /CD45.2 + spleen transplantation. Spleen‐derived CD11b + cells purified from fibrotic livers were then annotated by single‐cell RNA sequencing, and a subtype of CD11b + CD43 hi Ly6C lo splenic monocytes (sM‐1s) was identified, which was markedly expanded in both spleens and livers of mice with liver fibrosis. sM‐1s exhibited mature feature with high expressions of F4/80, produced much ROS, and manifested preferential migration into livers. Once recruited, sM‐1s underwent sequential transformation to sM‐2s (highly expressed Mif, Msr1, Clec4d, and Cstb ) and then to spleen‐derived macrophages (sMφs) with macrophage features of higher expressions of CX3 CR1, F4/80, MHC class II, and CD64 in the fibrotic hepatic milieu. Furthermore, sM‐2s and sMφs were demonstrated capable of activating hepatic stellate cells and thus exacerbating liver fibrosis. Conclusions: CD11b + CD43 hi Ly6C lo splenic monocytes migrate into the liver and shift to macrophages, which account for the exacerbation of liver fibrosis. These findings reveal precise mechanisms of spleen–liver axis in hepatic pathogenesis and shed light on the potential of sM‐1 as candidate target for controlling liver diseases. Abstract :